2021
DOI: 10.1186/s13052-021-01062-z
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Individual level and community level factors affecting exclusive breast feeding among infants under-six months in Ethiopia using multilevel analysis

Abstract: Background Exclusive breastfeeding (EBF) is the safest and healthiest option of feeding among infants in the first 6 months throughout the world. Thus, promotion of EBF is essential to prevent complex infant health problems even at the adulthood level. But majority of previous studies focused on individual level determinants of EBF by using basic regression models in localized areas. This study aims to identify individual level and community level determinants of EBF which would be helpful to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…In addition, the number of community-level factors that were investigated for their association with IYCF was small, given that the initial survey collected few of these variables. Future studies addressing community-level determinants of IYCF are encouraged to include additional factors such as community-level access to antenatal and postnatal care, community poverty level, community's media exposure and community-based BF promotion, support and advocacy (59) . Finally, it may be argued that the time that has elapsed between data collection (2012-2013) and the data analysis undertaken in this study (early 2021) may raise questions on whether the study findings are reflective of the current situation in the country.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the number of community-level factors that were investigated for their association with IYCF was small, given that the initial survey collected few of these variables. Future studies addressing community-level determinants of IYCF are encouraged to include additional factors such as community-level access to antenatal and postnatal care, community poverty level, community's media exposure and community-based BF promotion, support and advocacy (59) . Finally, it may be argued that the time that has elapsed between data collection (2012-2013) and the data analysis undertaken in this study (early 2021) may raise questions on whether the study findings are reflective of the current situation in the country.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of a systematic review were in accordance with the self-efficacy theory, wherein a mother’s confidence in her ability to breastfeed predicted her breastfeeding behavior [ 50 ]. Evidence also suggested that effective intervention strategies should include a multilevel approach since an individual’s knowledge, behavior, and attitudes were influenced by interactions between friends, family, and the community [ 50 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…17 The location of the baby's delivery was not significantly associated with EBF in this study. 17 Tsegaw et al 18 showed that institutional variables such as delivery at a healthcare facility, delivery assistance personnel present at the birth, and consistent antenatal/postnatal care, were significantly associated with an increased likelihood of EBF in Ethiopia. 18 While these maternal health services are greatly underutilized in Ethiopia and need further strengthening, they are still significantly associated with improving EBF practices, 19 but these types of interventions generally require specific timing.…”
Section: Practitioner Pointsmentioning
confidence: 99%